Perkembangan Fiksi Ilmiah Karya Pengarang Indonesia Tahun 1980-an dan 2000-an Pendidikan Bahasa dan Sastra Indonesia - Fitri Merawati (Kantor Bahasa Provinsi Maluku Utara, 2015)
This paper is aims at describing the development of science fiction, especially novel written by Indonesian Authors 1980s and 2000s. It is based on John Cawelty’s theory of Genre. The sample of science fiction works are Petualangan ke Planet Tau Ceti (The Adventure to the Planet of Tau Ceti) by H. Zubir Mukti, Penjelajahan Antariksa: Bencana di Planet Poa (Outer Space Adventure: disaster in the Planet of Poa), and Sabotase di Bulan (Sabotage Happened in the Moon) by Lia Cyntia. Science fiction works in 2000s are Dewi Lestari’s Supernova: Ksatria, Puteri dan Bintang Jatuh (Supernova: the Knight, The Princess, and the Falling Star), Andrea Hirata’s Laskar Pelangi (The Rainbow Troops), and Eliza V Handayani’s Area X (X Area). The Analysis technique is started from the text itself and then reveals the characteristics in the science fiction novel of Indonesian author in 1980s and 2000s. The result of analysis shows that the characteristics of formula in science fiction novels of Indonesian author in 1980s and 2000s have difference in the terms of theme, background, and plot. in 1980s’ novels, the theme and background mostly are in the outer space. Besides, the plot and characters are ordinary. Meanwhile, science fiction in 2000s, have some variations of theme based on the particular science development, the plot is more about daily life so that the imagination elements are less appear, as well as the complex characters. Therefore, science fiction is still developing. The difference of science fiction formula in 1980s and 2000s proves that to make a science fiction work needs special research and knowledge of the development of particular science which gives effect to the production of the science fiction.